2019
DOI: 10.5559/di.28.4.07
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personality Traits in the Choice and Use of Language Learning Strategies

Abstract: The paper aims to investigate the relationships between foreign language learning strategies (FLLS) and personality traits among students of education and engineering sciences. Quantitative survey of self-report questionnaire was used to evaluate learning strategies and individual personality traits. Pearson's correlation coefficients were calculated and six linear regressions were conducted to test the predictive role of personality dimensions when language learning strategies were used as a criterion. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Regarding the research designs identified, 34 investigations covered in this literature review can be considered non-intervention research. In this respect, 22 correlational studies attempted to associate LLS and other variables, such as learning characteristics [16], language proficiency [17], [18], [21], [27], [28], [41], [56], self-efficacy [19], [50], [53], self-regulation [23], [24], language learning beliefs [25], personality traits [29], learning styles [31], among others. Moreover, a total of 12 investigations can be categorized as survey research for they emphasize depicting the participants' use of LLS (e.g., [26], [30], [33], [35], [36], [40], [44], [48]).…”
Section: Methodology Of Research On Lls In Efl Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the research designs identified, 34 investigations covered in this literature review can be considered non-intervention research. In this respect, 22 correlational studies attempted to associate LLS and other variables, such as learning characteristics [16], language proficiency [17], [18], [21], [27], [28], [41], [56], self-efficacy [19], [50], [53], self-regulation [23], [24], language learning beliefs [25], personality traits [29], learning styles [31], among others. Moreover, a total of 12 investigations can be categorized as survey research for they emphasize depicting the participants' use of LLS (e.g., [26], [30], [33], [35], [36], [40], [44], [48]).…”
Section: Methodology Of Research On Lls In Efl Contextsmentioning
confidence: 99%
“…Moussa and Ghasemi [45] studied the interrelations between the strategies 50 undergraduate language learners take, their levels of self-efficacy, and their types of intelligence, where a significant correlation between LLS and self-efficacy was identified. As a further illustration, 382 undergraduates participated in an investigation of the relationships between LLS and personality traits [29]. The study claims that the selection of strategies varies depending on students' personality traits.…”
Section: Educational Settings In Lls In Efl Contextsmentioning
confidence: 99%
“…For instance, students with agreeableness mostly have a better ability to control emotions, so they tend to employ metacognitive strategies, which means such students adjust their learning status by understanding and controlling their cognition [3]. Extroversion students' vitality and confident characteristics make them positively correlated with affective strategies, this type of student is more inclined to peer cooperation, questioning for clarification, and other similar strategies to increase interest in learning [1,4]. What the students have to do is make full use of the unique academic strengths of a particular personality, or utilize appropriate learning strategies to heal their personality.…”
Section: Personality Corresponding Learning Strategies and Academic P...mentioning
confidence: 99%
“…They also found out that intuitive teachers, compared to sensitive ones, widely employ communication strategies. Safranj and Gojkov-Raji ( 2019 ) found out that individuals with various types of personality traits have distinct inclinations in choosing learning strategies. Low conscientious learners frequently use communication strategies, while learners with great mental powers widely use metacognitive and cognitive strategies.…”
Section: Major Concepts On the Spotlightmentioning
confidence: 99%